Review of current system & portfolio practices in the development sect or: Organizational… - Pereverza, Kateryna (2024)
Building on interviews with colleagues in development organizations, d onor & partner governments and foundations, this article explores the adoption of system and portfolio-based approaches in the development s ector focusing on organizational motivations and challenges, changes i n the network of the development sector actors, and types of collabora tive experiments initiated around the novel approach. The aim is to ta ke steps towards understanding how this type of approach for system ch ange can be institutionalized in the sector and become one of the main ways of operating for delivering transformative impact. Summary While there is a broad consensus that linear, fragmented, projectized ways of doing development & public policy are not a match for the type of c ontext we live in today, there is less consensus about what alternativ es look like. In this space, system and portfolio approaches have emer ged during the last few years and a new field is beginning to slowly e merge. Currently, there is a diversity in interpretations of system an d portfolio-based approaches by the development sector organizations. This is connected to different logics and theories of transformative c hange in complex systems. Also, the intent with the adoption of the no vel approach can vary along the dimension of organizational efficiency vs place-based transformations. Organizations engage with portfolio-b ased approaches with different intents and in different roles. For exa mple, OECD OPSI takes forward the innovation portfolio management for partners; the European Commission funds place-based portfolios e.g. wi thin the M4EG program; while UNDP facilitates place-based and thematic portfolios for system transformations. When it comes to the motivatio ns of development sector partners to experiment with system and portfo lio-based approaches, these include increased effectiveness & efficien cy of the use of funds for place-based transformations; response to th e post-colonial critique; creation of visibility as a frontrunner; the potential of joint risk-taking; the opportunity of collective learnin g from an entire portfolio (coherence & dynamic evolution); and direct ionality added to internal and external activities. Challenges encount ered by partners engaged in the experimentation with system and portfo lio-based approaches are connected to resources and time constraints t hat emerge from the prevailing logics & constraints of current organiz ational structures premised on fragmentation & projectization; organiz ational leadership dynamics; the influence of dominant organizational culture and mindsets; the difficulties of adopting the ‘portfolio lang uage’/jargon; prevailing funding structures and cycles; and a shortage of both time and capacity to engage with numerous local partners. The structure of the development sector ecosystem is undergoing changes d riven by a rapidly changing context. The experimentation with system a nd portfolio-based approaches has led to new actors joining the space, such as innovative consultancies developing the logic of transformati ve change in systems and facilitating portfolios on the ground, and th e emergence of new roles and relationships, for example, ‘learning par tners’. Since 2020, three noticeable types of collaborative experiment s emerged in the development sector ecosystem: systemic investments; t hematic and place-based portfolio interventions; and monitoring, evalu ation and learning (MEL) for the context of system change. This study revealed areas for further exploration and analysis. One is a need to co-create institutional structures to enable a co-ownership of place-b ased portfolios by several international partners as well as local sta keholders. Another area connects to the need to create and implement s paces and tools for collective learning from portfolios. Finally, ther e is a need to understand what mechanisms can enable the institutional ization of novel approaches on the level of the entire sector and thei r interconnection with organizational changes needed. This study is ba sed on the interviews with representatives of ten development sector o rganizations conducted in spring 2023 and insights shared within portf olio practitioner gatherings and the M&E Sandbox webinars run during 2 023. Introduction: The article emphasizes the importance of (re)framin g challenges in portfolio-based approaches for steering system transfo rmations. It acknowledges that the way we frame challenges significant ly influences the solutions we develop, and therefore, it’s crucial to address the right problems rather than wasting resources on incorrect issues. Study Insights: The insights come from a study initiated in a utumn 2021, focusing on how framing processes unfold, what needs to be framed, the open-ended nature of framing, and the roles international organizations like UNDP can play in developing inclusive and system t ransformation-oriented framings of urban challenges. Key Points: The s tudy involved interviews with experts from the UNDP Istanbul and Thail and Regional hubs. It explored the experimentation with the portfolio approach in collaboration with local and national governments and part ners. The article presents insights related to the framing process and highlights open questions for researchers and practitioners. System T ransformations: System transformations require a deep understanding be yond surface-level issues, as existing systems often limit our imagina tion and prevent us from exploring the root causes of complex societal challenges. Portfolio Approaches: The article references the collabor ation between the Swedish Strategic Innovation Programme “Viable Citie s” and the Strategic Innovation Unit of UNDP. They focus on portfolio- based approaches for urban low-carbon transitions in Sweden, targeting the mission: “Climate-neutral cities 2030 with a good life for all wi thin planetary boundaries.” Conclusion: The blog post concludes by hig hlighting the need for further research and practice in developing eff ective portfolio approaches to address complex societal challenges.